The Future of Classical Turkish Literature Studies in the Second Century of the Republic of Türkiye: Issues, Topics, and Duties - Mücahit Kaçar (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi, 2024)
In the context of the centenary celebrations of the founding of the Republic of Türkiye, researchers from different disciplines are seen to have evaluated studies related to their fields of expertise over the last century and to have written some accounting-type studies on what should be done in the future based on these. This study will touch on the possible research topics and issues that await classical literature researchers in the next century and point out the problems that need to be addressed in this field, the deficiencies to be filled, the mistakes to be corrected, and the work to be done. The study presents findings and suggestions on the following topics: The qualifications classical literature researchers should have, text identification and publication, intralingual translation, text analysis, the use of dictionaries in text commentaries, Turkish rhetoric, Sufi literature, literary genres, poetic studies, the Ottoman translation tradition, comparative studies, Chagatai Turkish texts, literary patronage, book culture and the importance of digital studies. The main text has avoided discussion of the subject and presentation of sources and pointed out sample studies suitable for suggestions in footnotes in order to directly point to the source of the problem regarding the issues being discussed and to draw researchers’ attention to findings and suggestions regarding these issues.